2000
DOI: 10.1016/s0968-8080(00)90004-1
|View full text |Cite
|
Sign up to set email alerts
|

Living with infertility: Experiences among urban slum populations in Bangladesh

Abstract: This paper explores the perceived causes of infertility, treatment-seeking for infertility and the consequences of childlessness, particularly for women, among a predominantly Muslim population in urban slums of Dhaka in Bangladesh. In-depth interviews were conducted with 60 women and 60 men randomly selected from Urban Surveillance System clusters of the International Centre for Diarrhoeal Disease Research, Bangladesh. Case studies of 20 self-perceived infertile women who had previously participated in a stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
82
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(96 citation statements)
references
References 8 publications
13
82
0
1
Order By: Relevance
“…These findings are consistent with other Asian studies of where women explained facing rude inquiries regarding their fertile capabilities and being termed as 'Manhoos', inauspicious and bearer of bad luck. 8,9 In present study participants expressed feeling of social pressure to conceive. Couples are pushed to have children as soon as possible and remedies and treatment suggestions are bombarded from all sides on young wife.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…These findings are consistent with other Asian studies of where women explained facing rude inquiries regarding their fertile capabilities and being termed as 'Manhoos', inauspicious and bearer of bad luck. 8,9 In present study participants expressed feeling of social pressure to conceive. Couples are pushed to have children as soon as possible and remedies and treatment suggestions are bombarded from all sides on young wife.…”
Section: Discussionmentioning
confidence: 66%
“…Studies conducted in India and Iran also showed that infertile women believed in a supreme power, accepted their infertility as God's will and result of their karmas of last birth. 8,14,15 where as in another study infertile women reported having lost faith in God due to struggle of infertility. 16 Participants in present study shared lack of financial support from in laws and no power of decision making which is similar to other study in South Asia where infertile women did not get proper care, refusal of food and clothing, abuse from husband and in laws and have to consult mother in law for treatment options.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Throughout much of sub-Saharan Africa, several reports [1] [2] indicate that infertility extends beyond the loss of human potential and unrealized self. It is a cause of physical, social and verbal abuse of couples affected.…”
Section: Introductionmentioning
confidence: 99%